Deep Extractive Oxidative Desulfurization of Model Oil/Crude Oil using Different Keggin Heteropoly Acids Supported on K10 Montmorillonite - Sadegh Sahraei; Ezzat Rafiee; Gholam Reza Moradi (Journal of Chemical and Petroleum Engineering, 2023)
This study investigated the catalytic performance of three polyoxometalates (H3PMo12O40 (PMo), H3PW12O40 (PW), and H4SiW12O40 (SiW)) supported on montmorillonite K10 for oxidative desulfurization (ODS) of thiophenic model oil, crude oil, and gasoline. Experimental results revealed that PW exhibited higher activity than PMo and SiW. The best solvent for mixed model oil was found to be EtOH, while MeCN was optimal for crude oil to remove oxidized sulfur compounds in a biphasic system under atmospheric pressure at 75°C in the presence of H2O2 as an oxidating agent. Using PW/K10 as the catalyst, the conversion of mixed model/EtOH and crude oil/MeCN reached 98.76% and 51.36%, respectively, under optimal conditions for 80 minutes. To investigate the impact of real oil composition on the desulfurization process, various unsaturated and N-compounds (pyrrole and pyridine) were added to mixed model oil. Finally, PW/K10 was recycled five times, and the results indicated no significant decrease in catalytic activity. Introduction